POST GRADUATE RESEARCH VIS-À-VIS FARMERS’ NEEDS – A STUDY IN THE FARM UNIVERSITY OF ANDHRA PRADESH - T. SRINIVAS (The Journal of Research ANGRAU, 2023)
The study conducted on the relevance of Post Graduate research in Acharya N.G. Ranga Agricultural University and Farmers Preference in Andhra Pradesh revealed that the PG Research is relevant to the farmers needs. However, the relevance was more in research pertaining to crop improvement and less in crop protection. In Crop Production, priority of the farmers was high on nutrient management (19.22 %), weed management (16.99 %) and soil biology & fertility management (12.26 %) and accordingly research was conducted.Research in organic agriculture, cropping & farming systems, soil and water pollution was not conducted as preferred by farmers. Research on interaction between biotic organisms, compatibility among the pesticide, fertilizers, herbicides need to be focused in view of farmers’ demand. Eventhough close relevance was observed between farmers needs and PG research in crop improvement, enough research in molecular biology & biotechnology was not conducted.The demand for research on training needs (19.67%) was more by the farmers while research is being conducted on production economics and farm management (25.00%).